Aircraft performance : an engineering approach - Sadraey, Mohammad H. (CRC Press, 2017)
"Flight is the process in which a vehicle moves through the air without any direct mechanical support from the ground. In Physics, science of the action of forces on material bodies is referred to as Mechanics. The science of "Mechanics" is basically divided into two branches: 1. Dynamics, and 2. Statics. Branch of mechanics that deals with the motion of objects in relation to force, mass, momentum, and energy is referred to as Dynamics. The topic of flight mechanics (or Flight Dynamics) is to study the motion of flying objects (e.g., aircraft, missile) through air"--Provided by publisher
Keywords: Airplanes -- Performance.; Aerodynamics.; elektronické knihy; electronic books